Evolusi Penggunaan Mata Uang Lokal Dalam Kerja Sama ASEAN Studi Kasus Indonesia, Malaysia, Dan Thailand - Farah Muthia Devi; Muhammad Sultan Ibrahimovic Sutisna; Natasha Putri Fedenan (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
By exploring international cooperation between Indonesia, Thailand and Malaysia in the use of local currency through the Local Currency Settlement (LCS) framework, this research details the deeper context regarding concerns regarding dependence on the US Dollar after the 2016-2017 financial crisis. with an emphasis on the development of the use of local currencies after the Asian crisis of 1997-1998. This research reveals that one of the main criteria for establishing an optimal currency area (OCA) is exchange rate stability. In looking at the research results, a positive evolution of the use of local currencies in post-crisis ASEAN cooperation is illustrated, especially through the LCS initiative involving Indonesia, Thailand and Malaysia. Although LCS implementation trends show positivity, further improvement is identified as an urgent need to bring it in line with total trade between countries. Hope lies in the LCS collaboration which is expected to strengthen currency stability, spur economic growth and increase trade activity in the region. Thus, this research provides valuable insight into the urgency of regional cooperation in managing dependence on global currencies, especially the US Dollar.